(untitled) (Research, Society and Development, 2021)
Aim: To evaluate the influence of three different working lengths on the amount of apically extruded debris. Methodology: Thirty lower premolars with single roots and straight root canals were standardized at 17 mm. Then, they were inserted into Eppendorf tubes, and the 1.5% agar gel was introduced into the tubes surrounding the roots. The coronal section of the roots was kept visible. The set of tubes and agar gel was weighed 3 times and the average value was recorded. Then, the specimens were randomly distributed in 3 different groups according to the working length (CT) used for the instrumentation: Group (CT -1) - the working length 1 mm below the major foramen (MF); Group (CT 00) - the length was determined at the MF, and Group (CT +1) - the CT was determined 1 mm beyond the MF. Instrumentation was performed with Reciproc Blue R25 (VDW, Munich, Germany) under irrigation with 0.9% saline. After preparation, samples were removed from Eppendorf tubes and weighed 3 times again. The difference between the mean values ​​of the initial and final weight was recorded. The one-way ANOVA test (post-hoc Bonferroni) was used with P> 0.05. Results: The average weight of the extruded waste was 0.0134 ± 0.0157 for CT -1, 0.0075 ± 0.0062 for CT 00 and 0.0075 ± 0.0068 for CT +1, with no statistically significant differences between groups. Conclusion: There was no impact of the different CTs on the amount of extruded debris beyond the apex.